Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1055/s-0042-112368
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide-1 Analogues Inhibit Proliferation and Increase Apoptosis of Human Prostate Cancer Cells in vitro

Abstract: Research has shown that the incidence of prostate cancer is increased in patients with type 2 diabetes mellitus (T2DM) 1. Glucagon-like peptide-1 (GLP-1) is a gastrointestinal hormone that enhances glucose-dependent insulin secretion and suppresses glucagon release. Here, we examined the effect of exenatide and liraglutide, 2 types of GLP-1 analogues, on prostate cancer cells growth by CCK-8 assay, Hoechst33258 staining assay, and western blot analysis of apoptosis-related proteins Bax and Bcl-2. Also the kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Both exenatide and liraglutide inhibited cell proliferation and increased apoptotic cell death in prostate cancer cells in a dose-dependent manner via an increase in the ratio of pro-apoptotic Bax/anti-apoptotic Bcl-2 and activation of the p38 MAPK-dependent cell death pathway [ 36 ]. Exenatide treatment reportedly exerted antiproliferative effects in the prostate cancer cell lines (LNCap, PC3, and DU14) and attenuated the growth of LNCap-derived xenografts in athymic mice [ 37 ].…”
Section: Possible Anti-cancer Effects Of Trzdmentioning
confidence: 99%
“…Both exenatide and liraglutide inhibited cell proliferation and increased apoptotic cell death in prostate cancer cells in a dose-dependent manner via an increase in the ratio of pro-apoptotic Bax/anti-apoptotic Bcl-2 and activation of the p38 MAPK-dependent cell death pathway [ 36 ]. Exenatide treatment reportedly exerted antiproliferative effects in the prostate cancer cell lines (LNCap, PC3, and DU14) and attenuated the growth of LNCap-derived xenografts in athymic mice [ 37 ].…”
Section: Possible Anti-cancer Effects Of Trzdmentioning
confidence: 99%
“…EXE and LIRA both inhibited the proliferation of endometrial carcinoma cells, through the AMPK signaling pathway [ 140 , 141 ]. The antiproliferative activity of EXE and LIRA has been reported on human prostate and hepatocellular carcinoma cells [ 142 , 143 ]. Thus, there is abundancy of preclinical data about the antitumorigenic effect of GLP-1 RAs.…”
Section: Cancermentioning
confidence: 99%
“…Liraglutide attenuates prostate cancer growth through regulation of the p38 pathway by binding with the GLP-1 receptor in vitro. 50 Forced expression of GLP-1 receptor attenuates prostate cancer cell proliferation by inhibiting cell cycle progression in vitro and in vivo. 51 A recent study also showed that an anticancer drug and liraglutide decreased the viability of prostate cancer cells (LNCaP) synergistically.…”
Section: Prostate Cancermentioning
confidence: 99%